Bullying Menjadi Budaya Pendidikan di lingkungan Pesantren - Fatiha Sabila Putri Matondang; Firman Firman; Riska Ahmad (Universitas Islam Sumatera Utara, 2022)
Bullying is a violent behavior both verbally and non-verbally that hurts someone or a group of people that is carried out by people who have more power and strength over other people. Of course this behavior is not good and has a bad impact on victims, but in fact this often happens in the world of education, including Islamic boarding schools. In fact, this has become a culture that is considered part of Islamic boarding school education where senior students who bully junior students even to the point of physical violence are referred to as seniority. This bullying behavior is inversely proportional to the Islamic religious sciences which form the basis of education in Islamic boarding schools where Islamic religious values that contain peace and mutual respect should be attached to the students so that it will prevent bullying. Seniority, victim grudges and the desire to be respected and want to be popular are the main factors in the emergence of bullying behavior.